1985
DOI: 10.1111/j.1432-1033.1985.tb08650.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential ADP‐ribosylation pattern of nucleosomal histones

Abstract: The pattern of nucleosomal histones poly(ADP-ribosy1)ation is changed under conditions which affect the poly(ADP-ribosy1)ation state of the enzyme. At low NAD concentrations the enzyme can poly(ADP-ribosy1)ate histones H1 and H1 O, H2A, A2A, and H2B. However at NAD concentrations above 10 yM the enzyme preferentially poly(ADP-ribosy1)ates histone H1 to a hyper ADP-ribosylated form. Furthermore we have observed hyper ADP-ribosylation of histone H2B at NAD concentrations of 10 yM suggesting that histone H2B can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…However, results obtained with reconstituted in vitro systems involving purified poly-(ADP-ribose) polymerase and appropriate chromatin acceptors have clearly shown that the pattern of (ADP-ribosyl)ated proteins (16) and the complexity (17) and size (17,18) of the (ADP-ribose)n polymer depend directly on the NAD' concentration in the reaction mixture. Similarly, the size of (ADP-ribose)n polymers generated in polynucleosomes by endogenous poly(ADP-ribose) polymerase depends on the NAD' concentration (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…However, results obtained with reconstituted in vitro systems involving purified poly-(ADP-ribose) polymerase and appropriate chromatin acceptors have clearly shown that the pattern of (ADP-ribosyl)ated proteins (16) and the complexity (17) and size (17,18) of the (ADP-ribose)n polymer depend directly on the NAD' concentration in the reaction mixture. Similarly, the size of (ADP-ribose)n polymers generated in polynucleosomes by endogenous poly(ADP-ribose) polymerase depends on the NAD' concentration (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The histone amino termini exposed on the nucleosome surface can be post-translationally modified by acetylation, 1 phosphorylation, 2,3 methylation, 4 ADP-ribosylation 5 and ubiquitination. 6 All core histones contain phosphoacceptor sites in their N-terminal domains: 7 H2A and H4 are phosphorylated on serine 1, H2B on serine 14 /32, H3 on serine 10/28 and threonines 3/11.…”
Section: Introductionmentioning
confidence: 99%
“…[3]) and the histone adducts thus formed can be further elongated by poly(ADPribose) polymerase [7]. Mechanistic interpretation of the enzymology of poly-ADP-ribosylation and of important supramolecular events in chromatin that appear to coincide with shifts in protein patterns of ADP-ribosylation [8,9] depend on a more detailed understanding of the initial steps of ADPribosylation at the poly(ADP-ribose) polymerase level [lo]. Pursuing this question, the existence of an early product [l l] was indicated.…”
Section: Introductionmentioning
confidence: 99%